Sexual Violence Tells Stories - Filaj, Anxhela (Hungarian Journal of English and American Studies, 2021)
Book review:Taylor, Dianna. Sexual Violence and Humiliation: A Foucauldian-Feminist Perspective. Abingdon: Routledge, 2020. 128 pages. ISBN 9781138581432. Pbk. N.p.